Abyssal fauna, benthic microbes, and organic matter quality across a range of trophic conditions in the western Pacific ocean. (July 2021) - Nomaki, Hidetaka; Rastelli, Eugenio; Alves, Andreia; Suga, Hisami; Ramos, Sandra; Kitahashi, Tomo; Tsuchiya, Masashi; Ogawa, Nanako O.; Matsui, Yohei; Seike, Koji; Miyamoto, Norio; Corinaldesi, Cinzia; et al.
Highlights: Abyssal Pacific sediments were characterized both geochemically and ecologically. Carbon fluxes affected abundance and biomass of large organisms most significantly. Large organisms had profound differences in abundances under different POC fluxes. Vertical distributions of labile organic matter coincided with organism distributions. Oligotrophic ecosystems may have more trophic levels than eutrophic ecosystems. Abstract: The abyssal plain covers more than half the Earth's surface. The main food source to abyssal ecosystems is phytodetritus, which originates from phytoplankton in the surface ocean, and thus its variability to the seafloor is a major driver of abyssal ecosystem biomass and functioning. In this study, we conducted a comparative survey on organic matter (OM) quality and quantity in abyssal plain sediments and examined the distributions of megafauna, macrofauna, meiofauna, prokaryotes, and viruses in eutrophic (39°N), oligotrophic (1°N), and ultra-oligotrophic (12°N) areas of the western Pacific. We also analyzed stable carbon and nitrogen isotopic compositions of organisms at 39°N and 1°N to assess differences in benthic abyssal food-web structures with contrasting trophic states. Sediments collected at 39°N presented highest concentrations of total organic carbon (TOC) and labile OM, and high diffusive oxygen uptake rates. By contrast, the lowest values were found at 12°N. Vertical distributions of sediment macrofauna, meiofauna, and prokaryotes matched with labile OM profiles. There were prominent differences in abundances of macro- and megafauna among stations with different OM fluxes, whereas the abundance of meiofauna and prokaryotes showed smaller differences among stations. Such differences could be explained by higher turnover rates of smaller organisms. Food-web structures of abyssal plains are likely influenced by both the type and size of primary producers in surface ocean. Our results underscore the crucial importance of OM fluxes and their compositions to the abundances and vertical profiles of labile OM and benthic biota in abyssal ecosystems.